PERAN DIGITAL MARKETING TERHADAP PENINGKATAN BRAND AWARENESS BANK SYARIAH: STUDI KASUS MASYARAKAT CIAMIS - Harun Nur Jamiel; Nurfaisyal Suryaeltarlan; Rida Taupik Hidayat (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2026)
The low level of Islamic banking literacy among the religious community of Ciamis Regency demands concrete innovations in adaptive marketing communication strategies within this digital information age. This study primarily aims to analyze and describe the strategic role of digital marketing in increasing the overall brand awareness of Islamic banks among Ciamis people. The research method used is a descriptive quantitative approach through field survey methods. The research sample includes one hundred random respondents determined through the application of simple random sampling techniques from various districts across Ciamis Regency. Primary data collection was conducted by distributing structured online questionnaires to the target audience. Furthermore, the data analysis technique utilizes a simple linear regression test to measure the real influence of digital marketing variables on brand awareness with the help of a computer statistical program. Empirical field findings clearly indicate that digital marketing has a positive and significant influence on raising the level of sharia banking brand awareness among the local community. Financial education content packaged with sharia values and interactive visual promotions are dominant factors proven to strengthen public memory toward the actual existence of Islamic financial institutions. The implications of this study confirm that optimizing digital media does not only function as a mere business instrument, but also acts as an effective contemporary preaching medium to massively expand the reach of sharia financial inclusion.